2022
DOI: 10.1200/jco.21.01745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Antiracism Intervention on Racial Disparities in Time to Lung Cancer Surgery

Abstract: PURPOSE Timely lung cancer surgery is a metric of high-quality cancer care and improves survival for early-stage non–small-cell lung cancer. Historically, Black patients experience longer delays to surgery than White patients and have lower survival rates. Antiracism interventions have shown benefits in reducing racial disparities in lung cancer treatment. METHODS We conducted a secondary analysis of Accountability for Cancer Care through Undoing Racism and Equity, an antiracism prospective pragmatic trial, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 45 publications
1
57
0
Order By: Relevance
“…Moreover, findings from a recently published study using ACCURE data revealed that the ACCURE intervention also addressed racial and ethnic gaps in treatment delays. 35 Critical to the ACCURE intervention was the real-time warning system, which alerted nurse navigators when a patient missed a recommended clinical milestone. This health informatics-enabled tool facilitated improved race-and ethnic-specific transparency and accountability in the delivery of recommended care to patients by prompting the clinical care team to re-engage and support the patient (e.g., address transportation barriers) toward receiving timely treatment when important care milestones were missed.…”
Section: Technologies To Reduce Provider Biasmentioning
confidence: 99%
“…Moreover, findings from a recently published study using ACCURE data revealed that the ACCURE intervention also addressed racial and ethnic gaps in treatment delays. 35 Critical to the ACCURE intervention was the real-time warning system, which alerted nurse navigators when a patient missed a recommended clinical milestone. This health informatics-enabled tool facilitated improved race-and ethnic-specific transparency and accountability in the delivery of recommended care to patients by prompting the clinical care team to re-engage and support the patient (e.g., address transportation barriers) toward receiving timely treatment when important care milestones were missed.…”
Section: Technologies To Reduce Provider Biasmentioning
confidence: 99%
“…Additional interventions using lay health navigators to decrease disparities in lung cancer care are ongoing. 14 The study by Charlot et al 15 in the article that accompanies this editorial reports the impact of a multilevel intervention, the Accountability for Cancer Care through Undoing Racism (ACCURE), on surgical delays (defined as . 8 weeks from diagnosis) among Black versus White patients with stage I and II nonsmall-cell lung cancer.…”
mentioning
confidence: 99%
“…In the article that accompanies this editorial, Charlot et al 15 describe the association of a multilevel intervention, the Accountability for Cancer Care through Undoing Racism, with a reduction in delays in resection among Black patients with stage I and II lung cancer. These results suggest that implementation of real-time notifications of incomplete treatment milestones, physician feedback about racial gaps in treatment rates, and patient navigation may improve lung cancer outcomes among minority patients with early-stage disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a recent example, an antiracism system–based intervention was recently demonstrated to eliminate racial disparities in timeliness of lung cancer surgery. 11 The intervention consisted of a real-time warning system using the electronic health record to measure time-sensitive clinical milestones and enhance race-specific transparency in adhering to standards of care, a physician champion who reviewed quarterly reports on race-specific treatment completion rates, and a nurse navigator trained in racial equity analysis who informed the clinical team of care delays and addressed patient barriers to care such as lack of transportation or misinformation. This type of multilevel intervention serves as a model for reducing racial disparities in treatment and could also be applied to clinical trial enrollment.…”
mentioning
confidence: 99%